Виготовлення і характеристика стекол з боратів цинку і барію, допованих Sm3+ - Yamsuk, Y.; Yasaka, P.; Sangwaranatee, N.; Keawkao, J. (Publishing house "Academperiodika", 2018)
Zinc-barium-borate glasses with the composition (60 − x)B2O3–10ZnO–30BaO–xSm2O3 (where x = 0.5, 1.0, 1.5, 2.0 and 2.5 mol %) doped with Sm3+ ions have been prepared, and their physical and optical properties are investigated. The photoluminescence spectra recorded under the 403-nm excitation exhibited the emission bands at 564, 600, 647, and 710 nm corresponding to the transition 4 G5/2 →6 Hj (j = 5/2, 7/2, 9/2, 11/2), respectively. Judd–Ofelt intensity parameters (Ωl, l = 2, 4 and 6) have been evaluated, and the radiative transition probabilities, emission cross-section, and branching ratios for the excited levels of Sm3+ ionsare predicted. The lifetime of the 4 G5/2 level is found to decrease with an increase in the Sm3+ ion concentration.